2018
DOI: 10.22270/jddt.v8i1.1555
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone as Drug Carrier for an Antifungal Agent

Abstract: One of the most suitable and most used biodegradable polymers in particulate drug delivery is Polycaprolactone. This could be attributed to its several important characteristics including its low degradation rate, high permeability and low toxicity. In this study, Polycaprolactone microspheres loaded with the antifungal agent Amphotericin B were synthesized by means of the solvent evaporation method. The prepared microspheres had homogeneous particle sizes between 110 and 125 µm. they also showed a porous stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Owing to its high permeability for small drug molecules [10], the aliphatic polyester, PCL represents an important candidate for fabricating carriers for drug delivery applications, including: microparticles [11], nanoparticles [12], microspheres [13], coatings [14], and scaffolds [15]. However, due to its intrinsic high hydrophobicity and crystallinity, PCL degrades rather slowly.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high permeability for small drug molecules [10], the aliphatic polyester, PCL represents an important candidate for fabricating carriers for drug delivery applications, including: microparticles [11], nanoparticles [12], microspheres [13], coatings [14], and scaffolds [15]. However, due to its intrinsic high hydrophobicity and crystallinity, PCL degrades rather slowly.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydrophobic property of PCL causes delay in the penetration of water and therefore the diffusion of the drug through the amorphous region is delayed 67 . Moreover, it has been reported that the PCL is more hydrophobic than other 68 . This feature makes its degradation very slow in aqueous medium, and in return suitable for controlled and sustained drug release.…”
Section: Resultsmentioning
confidence: 99%
“…67 Moreover, it has been reported that the PCL is more hydrophobic than other. 68 This feature makes its degradation very slow in aqueous medium, and in return suitable for controlled and sustained drug release.…”
Section: Drug Release In the Optimal Formulationmentioning
confidence: 99%
“…Carbon nanomaterials, such as the activated carbons, can meet the standard criteria for good adsorption because they have a high surface area, a big pore volume, and are characterized by strong physicochemical interactions with the pollutants [5]. Modeling of the adsorption process was previously performed in order to find a clear relation between the experimental adsorption isotherm and the theoretical model, as well as with the values of the energy of adsorbate interaction with the surface [6,7]. For description of the adsorption mechanism by an individual model expression, we usually used the most known models such as Langmuir, Freundlich, and Langmuir-Freundlich models [8].…”
mentioning
confidence: 99%